A comment on changes in the Norwegian Land Consolidation Act - Per Kåre Sky (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2018)
The Land Consolidation Act has recently been revised. The changes came into force on 1 July 2006 and 1 January 2007. The main changes in the Act are that the land consolidation court now has formal jurisdiction to handle land consolidation cases for all types of properties independent of location, unless particular cases are specifically removed from the court's jurisdiction in the Act. The Act provides for two new types of land consolidation cases in Section 2. The paper analyzes these different revisions.
Keywords: P48; Q15; 330; Land consolidation; Land consolidation court; Urban areas